Resposta imune em cães experimentalmente infectados por Rangelia vitalii - Paim, Francine Chimelo (2013)
Rangelia vitalii is the etiologic agent of rangeliosis, a hemorrhagic disease that was described in dogs from South and Southeast Brazil, Uruguay and Argentina. The immunological aspects involved in this disease have not been fully elucidated. This study aimed to investigate the immunological parameters in rangeliosis by the determination of serum cytokines, nitric oxide, electrophoretic profile, acute phase proteins and immunoglobulins of dogs experimentally infected with R. vitalii. Twelve dogs were divided into two groups: Group A (control) composed by uninfected animals (n=5) and Group B consisting of animals inoculated with R. vitalii (n=7). After inoculation, animals were monitored by blood smear. Blood samples were collected through the jugular vein on days 0, 10 and 20 post-inoculation (PI) to determine the serum levels of interferon-gamma (IFN-γ), tumor necrosis factor-alpha (TNF-α), interleukin 1 (IL-1), interleukin 6 (IL-6), oxidation products of nitric oxide (NOx), electrophoretic profile, acute phase proteins (C-reactive protein and alpha 1 acid glycoprotein) and immunoglobulins (IgG, IgM, IgA and IgE). The parasite was found within erythrocytes, neutrophils and monocytes on day 5 PI in infected group. This study showed an increase (P<0.01) of cytokines levels in the infected group when compared to control group. Serum levels of NOx increased on days 10 (P<0.01) and 20 PI (P<0.05) in infected animals. Total protein decrease on days 10 (P<0.01) and 20 (P<0.05) PI. There was a reduction (P<0.01) in albumin in infected group when compared with control group. Alpha-1 globulin and gamma globulin fractions increased (P<0.01) on day 20 PI in infected animals. Alpha-2 globulin (days 10 and 20 PI) and beta-2 globulin (day 10 PI) were decreased (P<0.05) in infected animals when compared to control group. Beta-1 globulin fraction did not differ statistically. Serum C-reactive and alpha 1 acid glycoprotein concentrations increased (P<0.05) on days 10 and 20 PI in infected animals. IgG was increased on days 10 (P<0.05) and 20 PI (P<0.01) in infected animals. It was observed an increase (P<0.01) in the levels of IgM, IgA, and IgE in infected animals compared to control group. From these results, we can conclude that rangeliosis causes alterations in serum cytokines, nitric oxide metabolites, serum proteins and stimulates the synthesis of acute phase proteins and immunoglobulins. These alterations may be associated with the host immune protection against the piroplasms, similar to what occurs in other hemoparasite infections.